Public finance in underdeveloped countries - Prest, A. R. (London : Weidenfeld and Nicolson, 1972)
The study starts by examining the differences between tax/income (or expenditure /income) ratios in developing and advanced countries and then look at the possible explanations of any such discripancies
Bibliography: p. 202-203.
sju 22/01/2019
Loans
Keywords: Finance, Public